The study of oat varieties (Avena sativa L.) of various geographical origin for grain quality and productivity - V. I. Polonskiy; N. A. Surin; S. A. Gerasimov; A. G. Lipshin; A. V. Sumina; S. Zute (Вавиловский журнал генетики и селекции, 2019)
In order  to identify samples  with a minimum  and  maximum  content of β-glucans  in the  grain, screening of oats grown in Eastern Siberia for three  years was performed. To determine the prospects for further use of oat samples, other chemical, physical and production characteristics were measured in parallel: the protein  and oil content in the grain, its film content, test weight, 1000 grains weight, the vegetation period and the yield. The object of a comprehensive evaluation was 14 hulled and naked 5 VIR (N.I. Vavilov All-Russian Institute of Plant Genetic Resources) oats samples of different origin, mainly from Siberia. The hulled samples formed grains with β-glucan content from 2.9 to 5.2 %, while the naked ones, from 3.7 to 4.8 %. The lowest values were in the Krasnoyarsk varieties Tubinskiy, Kazyr, Sayan (about 3 %); the highest, in the foreign accession Local Tunisia 1 (5.2 %). The highest oil content was shown by Tubinsky, Kazyr and Sayan, all currently cultivated in the Krasnoyarsk region. An increased accumulation of protein in grain was observed in the hulled variety Local Tunisia 1 and the naked accession of Vyatskiy. According to the content of β-glucans  in the grain, taking into account its other characteristics and yield values, the best samples for the food direction (the maximum level of these substances) are Local Tunisia 1, Medved and Taidon, and for feed use (the minimum level) are Tubinskiy, Vyatskiy and Golets. There was no noticeable advantage of naked samples  in comparison with hulled ones in the content of β-glucans  in the grain. A high strength of the positive relationship between the content of oil or β-glucans  in the grain and the year of oat cultivation was observed in the hulled samples. In naked forms, a clear link between the concentrations of chemicals in the different  grain samples  of oats and the year of cultivation has not been established.